Progressive symmetric erythrokeratodermia with delayed intellectual milestones and convulsions - Shyam B Verma; Uwe Wollina (Wolters Kluwer Medknow Publications, 2012)
Progressive symmetric erythrokeratoderma is an uncommon genodermatosis and is thought to arise due to mutations in the connexin gene, however, genetic heterogenicity has been described. Very few cases of neurological involvement have been described in this unusual entity. We report a case of progressive symmetric erythrokeratoderma, with convulsions and delayed intellectual milestones.